2022
DOI: 10.3389/ffgc.2022.913127
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Partitioning and Dynamics in Coriaria nepalensis Wall Dominated Shrublands of Degraded Hills of Kumaun Himalaya

Abstract: Coriaria nepalensis is one of the shrubs which have the ability to mitigate the frequency of perilous natural events or natural calamities. This paper elucidates the nutrient dynamics of C. nepalensis shrublands in degraded hills of Kumaun Himalaya. The average nutrient concentration (N, P, and K) in aboveground components of C. nepalensis was in the following order: Foliage > Twigs > Branches > Bole wood, whereas in belowground components the order was: Fine roots > Lateral roots &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Soil C and N dynamics are influenced by climate, soil texture, land‐use patterns, vegetation and ecosystem management (Awasthi et al., 2022; Cai et al., 2016; Dang et al., 2022; Pant et al., 2017). Soils of different fertilities responded positively to N fertilization by increasing soil C and N (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil C and N dynamics are influenced by climate, soil texture, land‐use patterns, vegetation and ecosystem management (Awasthi et al., 2022; Cai et al., 2016; Dang et al., 2022; Pant et al., 2017). Soils of different fertilities responded positively to N fertilization by increasing soil C and N (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we estimated microbial turnover based on changes in the soil microbial biomass pool during crop rotation and found that microbial turnover was related to the level of microbial biomass, with little difference in its turnover rate (Tables S3 and S4). (Awasthi et al, 2022;Cai et al, 2016;Dang et al, 2022;Pant et al, 2017). Soils of different fertilities responded positively to N fertilization by increasing soil C and N (Table 3).…”
Section: Soil Microbial Biomassmentioning
confidence: 99%
“…The detailed description of the litter fall estimation of the C. nepalensis dominated sites is given in Awasthi et al (2022b). For the assessment of the decomposition rate and nutrient dynamics of the different components of the same, litter bag technique, which is a direct method of measuring decomposition rate, was used to observe the litter decomposition (Awasthi et al, 2022c). Nearly senesced but attached plant leaves, twigs (twigs < 5 mm and twigs > 5 mm), bark, fine roots, lateral roots, and reproductive parts were collected from the plant and air dried till the constant weight was not achieved.…”
Section: Decomposition Processesmentioning
confidence: 99%
“…C. nepalensis is a common native shrub species of Yunnan Province that grows between 1200 and 2500 m a.s.l. (Awasthi et al, 2022b). A previous study (Mourya et al, 2019) showed that C. nepalensis could accumulate nutrients and thus aid the colonization of additional plants and contribute to the recovery of degraded forest ecosystems in the central Himalaya.…”
Section: Introductionmentioning
confidence: 99%